Social support as coping mechanism mediates the relationship between eco-anxiety and pro-environmental behavior. - Veera Nieminen; Sonja Palmo; Katriina Hyvönen; Jane-Veera Paakkolanvaara; Kaisa J Raatikainen; Joona Muotka (PLoS ONE, 2025)
We studied social support as a coping strategy for eco-anxiety. Furthermore, we investigated the moderating or mediating role of social support in the relationship between eco-anxiety and pro-environmental behavior (PEB). The participants were Finnish adults aged 19-42. Most of the participants were women (76.2%), lived in an urban environment (82.7%), and were students (47.4%) or employees (42.8%). Data collected with an online survey was analyzed using correlation analysis, hierarchical regression analysis, and a simple mediation model. We found that experiencing eco-anxiety was positively related to PEB, and that the participants with higher social support had higher levels of eco-anxiety. In addition, using social support as a coping strategy was connected to a higher level of PEB. We found that social support mediates the positive connection between eco-anxiety and PEB, but no moderating effect was found. Our results imply that social support can be an important coping strategy for adults coping with eco-anxiety, as well as promoting PEB, offering an interesting insight for future interventions.